Coagulation Factor VII in Middle-aged Women with and without Coronary Heart Disease - Eriksson-Berg, Margita; Silveira, Angela; Orth-Gomér, Kristina; Hamsten, Anders; Schenck-Gustafsson, Karin (Thrombosis and Haemostasis, 2001)
Epidemiological studies of coagulation factor VII as a risk factor for coronary heart disease (CHD), mainly conducted in men, have shown discrepant results. We examined the associations of coagulation factor VII antigen (VIIag) and activated factor VII (VIIa) with manifest CHD in a community-based case-control study of women aged ≤65 years. Mean plasma concentrations of VIIag and VIIa in patients and controls were 443 ± 108 and 418 ± 89 ng/L (p <0.01) and 5.26 ± 2.21 and 4.90 ± 1.65 ng/L (NS), respectively. The odds ratio (OR) for CHD for the highest versus the lowest quartile of VIIag was 1.75 (95% CI, 1.05 to 2.92). The adjusted OR was 0.76 (95% CI, 0.28-1.98) after controlling for other cardiovascular risk factors. The corresponding ORs for VIIa were non-significant. In conclusion, the plasma concentration of VIIa was not significantly increased in a large group of women with precocious CHD, and VIIag levels, although elevated, were not independently associated with manifest disease.
Keywords: Factor VII; lipoproteins; risk factors; myocardial infarction; coronary heart disease